Upper Gastrointestinal Bleed due to Duodenal Metastases of Lung Adenocarcinoma: Report of Two Cases and Review of Literature - Sumitro Kosasih; Khairul Najmi Muhammad Nawawi; Zhiqin Wong; Deborah Chew Chia Hsin; Andrea Yu-Lin Ban; Raja Affendi Raja Ali (Case Reports in Medicine)
Upper gastrointestinal bleeding as a result of gastrointestinal metastases from lung cancer is extremely rare. We report two cases of patients with duodenal metastases from lung adenocarcinoma presented with recurrent melena. Histopathological examination and immunohistochemical staining of the duodenal biopsies supported the diagnosis of metastatic lung adenocarcinoma.